A Study Of The Special Features Of The Meniscal Tear - Zorigtbaatar, Orgil; Dagvasumberel, Gonchigsuren; Lkhagvasuren, Naranbat; Sosor, Baatarjav (Central Asian Journal of Medical Sciences, 2023)
Objectives: Arthroscopic meniscectomy is a treatment with good short-term results. To prevent the long-term adverse effects of meniscal tear injuries, it is necessary to study the unique features, such asthedemographic characteristics of the injury, the cause of the occurrence, and the type and location of the tear. Methods: We conducted the hospital-based prospective study and involved 103 patients who underwent arthroscopic knee surgery at The National Trauma Orthoped ic Research Center and Grandmed Hospital in Mongolia between 2020 and 2022. We classified Cooper’s classification based on MRI results. Moreover, the type and location of the meniscal tear were finally determined by the diagnosis after arthroscopic surgery. Results: Out of 103 patients, the mean age of the participants was 34.4±8.6 (18-48 years); males were 61.2% (n=63), and 87.7% (n=93) of tears were located in the medial meniscus, respectively. Among the types of tears, the most frequent were the vertical tears, especially the Radial/Transverse and Vertical/Longitudinal 20% (n=18) tears. Conclusion: The causes of meniscal tears are mainly injuries. Men are injured more by sports injuries and women by domestic injuries. The type and location of the isolated meniscal tears differ from those of the meniscal tears.